2007
DOI: 10.2165/00002018-200730120-00005
|View full text |Cite
|
Sign up to set email alerts
|

Bodyweight Changes Associated with Antihyperglycaemic Agents in Type 2 Diabetes Mellitus

Abstract: The majority of patients with type 2 diabetes mellitus are overweight or obese at the time of diagnosis, and obesity is a recognised risk factor for type 2 diabetes and coronary heart disease (CHD). Conversely, weight loss has been shown to improve glycaemic control in patients with type 2 diabetes, as well as to lower the risk of CHD. The traditional pharmacotherapies for type 2 diabetes can further increase weight and this may undermine the benefits of improved glycaemic control. Furthermore, patients' desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(122 citation statements)
references
References 91 publications
3
115
1
3
Order By: Relevance
“…It also showed that patients who gained most weight during the study (median BMI change+3.8 kg/m 2 ) had a 1.8-to 2.3-fold increase in risk of CHD compared with those who gained less weight or who lost weight. Weight change with regard to diabetes is a complex topic, as weight loss could reflect poorly controlled diabetes (few in this study), and weight gain could be attributable to pharmacological treatment to improve metabolic control [34]. The latter was accounted for by adjusting for the type of hypoglycaemic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It also showed that patients who gained most weight during the study (median BMI change+3.8 kg/m 2 ) had a 1.8-to 2.3-fold increase in risk of CHD compared with those who gained less weight or who lost weight. Weight change with regard to diabetes is a complex topic, as weight loss could reflect poorly controlled diabetes (few in this study), and weight gain could be attributable to pharmacological treatment to improve metabolic control [34]. The latter was accounted for by adjusting for the type of hypoglycaemic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While reduction of hyperglycaemia remains the foremost goal in the pharmacological treatment of T2DM, the avoidance of weight gain may be a clinically important secondary goal 20 .…”
Section: Impact Of Glucose Control On Body Weight Regulationmentioning
confidence: 99%
“…This suggests that, for Japanese T2DM patients, the addition of either biguanide or TZD to sulfonylurea does not necessarily improve glycemic control. It has been reported that the metformin monotherapy reduced body weight and reversed the weight gain by sulfonylurea in combination with sulfonylurea, while BMI of the patients treated with sulfonylurea alone compared with sulfonylurea plus metformin was variable [26,27]. Our study was not longitudinal and could not detect the changes in body weight, therefore, we could not discuss the desirable effect of metformin on BMI.…”
Section: Acknowledgementsmentioning
confidence: 78%